Kalça artroskopisi: Haseki deneyimi - Kaya, İbrahim; Uğraş, Akın; Sungur, İbrahim; Yılmaz, Murat; Bayram, Erhan; Ertürk, Ahmet; Çetinüs, Ercan (My University, 2013)
Amaç: Anatomik olarak derin yerleşimli ve rijit olan kalça eklemi ve çevresinin patolojilerinin tanısı ve tedavisinde kalça artroskopisinin yeri irdelendi ve klinik tecrübelerimiz paylaşıldı. Gereç ve Yöntem: 2011 ve 2012 yılları arasında kliniğimize aksama ve kasıkta ağrı nedeni ile başvuran kalça artroskopisi yapılan hastalar değerlendirildi. Ortalama yaş 35.8 (alt-üst sınır: 17-58)yıl olan olguların üçü bayan, 12’si erkek 15 olgu değerlendirildi. Olguların ameliyat öncesi ve sonrası Harris kalça skoruna bakıldı. Bulgular: Olguların ortalama Harris kalça skoru ameliyat öncesi 62.7 (54-86) iken, ameliyat sonrası 92.5 (82-100) olarak saptandı. Üç hastamızda CAM tipi sıkışma saptanıp traşlandı, beş hastada labrum yırtığı saptanıp ikisi dikildi, diğerleri debride edildi. Bir hastada osteokondral lezyon(OCD) saptanıp ters mozaikoplasti yapıldı. Bir hastada lokalize femur başı avasküler nekroz saptanarak anterior mini açık mozaikoplasti yapıldı. İki hastada eklem içinden serbest cisim, bir hastada eklem içi mermi çıkarıldı. İki hastada eklem içi patoloji saptanmadı. Sonuçlar: Kalça artroskopisi eklem içi ve çevresindeki patolojilerin tanı ve tedavisinde deneyimli ellerde yapıldığı zaman iyi sonuçlar veren minimal invaziv bir tanı ve tedavi yöntemidir. Tekniğin başarısı yüksek olmakla birlikte nörojenik komplikasyonlar açısından cerrah portal yerleşiminde dikkatli olmalı, traksiyon süresini kısa tutmaya çalışmalıdır.

Objective: Hip is a relatively rigid and deep located joint. The role of arthroscopy in diagnosis and treatment of hip and surrounding tissue pathologies has been evaluated along with our clinical experience. Material and Method: Fifteen hip arthroscopy cases who had admitted to our clinic with antalgic limp and groin pain between 2011 and 2012 were evaluated. Mean age was 35.8 (17-58) years. Three of the patients were female and 12 were male. Preoperative and postoperative Harris hip scores were recorded. Results: Mean preoperative Harris Hip Score of the cases was 62.7 (54-86) and mean postoperative Harris Hip score was 92.5 (82-100). In three patients CAM type femoro-acetabular impingement was diagnosed and excessive portion of the femoral neck was shaved. In five patients, labral tears were detected. Two were repaired and three were debrided. One patient was diagnosed with osteochondral lesion and treated with reverse mosaicoplasty. Localised avascular necrosis of the femoral head was diagnosed in one patient and anterior mini-open mosaicoplasty was performed. Loose bodies were excised in two patients and intraarticular bullet was extracted in one patient. In two patients, no intraarticular pathology was detected. Conclusion: When performed by experienced surgeons, hip arthroscopy is a minimal invasive diagnostic and treatment method which has successful results in intraarticular and periarticular hip disorders. Despite the high success rate, neurologic compromise must be avoided by paying meticulous attention in portal selection and by keeping the traction time as short as possible.
Hip arthroscopy: The haseki experience
Keywords: Kalça Eklemi; Artroskopi; Labrum; Debridman; Hip Joint; Arthroscopy; Labrum; Debridement